MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DI MTs NEGERI 2 MEDAN SUMATERA UTARA - Hadi Purnomo; Camelia; Amelia Ardan Tambunan; Hapni Hasibuan (CV. Arsy Persada Quality, 2024)
This research examines the implementation of management of educational facilities and infrastructure at MTS Negeri 2 Medan. The aim of this research is to determine the implementation of management of educational facilities and infrastructure at MTs Negeri 2 Medan in the Planning, Use and Maintenance of facilities and infrastructure section. This research uses a qualitative approach with a descriptive research type with research subjects including the Deputy Principal of the school in the field of facilities and infrastructure. Data collection uses interviews, observation and documentation. The data obtained was analyzed through data reduction, data presentation, and drawing conclusions. The results of the research show that: (1) Planning for educational facilities and infrastructure at MTs Negeri 2 Medan by looking at and classifying consumable and non-consumable items and planning is carried out at the start of each new lesson. So the principal, deputy principal in the field of facilities and infrastructure and administration make initial observations to see the school needs proposed by the teachers and see what needs are the most urgent. (2) One way of using facilities and infrastructure is by making a schedule for their use. For example Laboratory The IPA who makes the schedule is the head of the Laboratory IPA. (3) Maintenance of facilities and infrastructure at MTs Negeri 2 Medan, with maintenance carried out every day, cleaning classrooms, courtyards, tables, chairs and toilets. As for other treatments, if an item is damaged but the item needs to be used, it is included in emergency care. Maintaining facilities and infrastructure at MTs Negeri 2 Medan has a special expert who is given responsibility for maintaining facilities and infrastructure so that the school principal is not too burdened.